ANALISIS VIRTUAL REALITY PADA GAME VR CALL OF DUTTY DI GAME BLINK PADANG - Fadhil Daifullah; M. Baitul Arifin, Muhammad Riski Swandi, Mohamad Halim, Rusdi Asmi Al Akila, Wahyu Pratama, Rini Nov (ADISAM PUBLISHER, 2024)
The integration of Virtual Reality (VR) technology into the Call of Duty gaming franchise has brought about significant advancements in gameplay experience and player engagement. VR technology enables players to immerse themselves more deeply into the game environment, enhancing realism and emotional involvement. This study examines various aspects of VR implementation in Call of Duty, including technological advancements, gameplay impacts, and player perceptions.Technological advancements in VR have facilitated a more immersive gaming experience through devices like Oculus Rift and HTC Vive, providing players with 360-degree visual environments and enhanced sensory interactions. VR enhances gameplay in Call of Duty by allowing players to experience battles with heightened realism and strategic complexity, though it also presents challenges such as motion sickness and gameplay adjustments. Player responses to VR in Call of Duty vary widely, with some embracing the enhanced immersion while others face adaptation challenges. The study highlights the importance of optimizing game performance to ensure smooth visuals and reduce player discomfort, as well as designing intuitive interfaces and gameplay mechanics tailored for VR. Overall, the study underscores VR's potential to revolutionize gaming by providing deeper, more engaging experiences. Future research should continue exploring VR's long-term eflects on player behavior and health, while developers innovate to overcome technical challenges and expand VR accessibility